2015
DOI: 10.1002/cncr.29153
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical factors associated with obesity among adult survivors of childhood cancer: A report from the St. Jude Lifetime Cohort

Abstract: Purpose We aimed to identify treatment and genetic factors associated with obesity among childhood cancer survivors. Methods Participants included 1996 survivors previously treated for cancer at St. Jude Children’s Research Hospital who survived ≥10 years from diagnosis (median age at diagnosis 7.2 years, median age at follow-up 32.4 years). Obesity was defined as a body mass index ≥30kg/m2. Factors associated with adult obesity were identified by subgroup-specific (cranial radiation (CRT) exposure status) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 38 publications
(74 reference statements)
7
78
1
Order By: Relevance
“…Our finding that there was no increase in BMI z-score in patients with chemotherapy and radiation therapy is inconsistent with that of prior studies which have found that injury to the CNS via radiation [2,3,5,7,8,20,24,27] and chemotherapy [3] is associated with increased likelihood for obesity. One possibility for the discrepancy is the difference in dose of radiation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that there was no increase in BMI z-score in patients with chemotherapy and radiation therapy is inconsistent with that of prior studies which have found that injury to the CNS via radiation [2,3,5,7,8,20,24,27] and chemotherapy [3] is associated with increased likelihood for obesity. One possibility for the discrepancy is the difference in dose of radiation.…”
Section: Discussioncontrasting
confidence: 99%
“…Self-report data from the CCSS are supported by self-report measures in other cohort studies [10]. However, data from clinical cohorts, where BMI is ascertained using objective measures, indicate obesity rates ranging from 31% at a mean age of 22.3 years [11] to 42.8% at a median age of 32.4 years [12]. These rates are higher than expected given that the proportion of 20–39 year olds in the general population who are obese is 30.3% [13].…”
Section: Obesitymentioning
confidence: 99%
“…The most frequently documented risk factors for obesity following treatment for childhood ALL are CRT, younger age at diagnosis, and female sex [11, 8, 12]. In the CCSS, females who received CRT doses in excess of 20 Gy had the highest odds (OR 3.81, 95% CI 2.34–5.99) of obesity when compared to siblings [8].…”
Section: Treatment-related Risk Factors For Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…An example is the evaluation of genetic predictors of clinically ascertained outcomes in the SJLIFE cohort 9 , a study among childhood cancer survivors treated at St. Jude Children’s Research Hospital (SJCRH), who have survived 10 or more years from diagnosis and are at least 18 years of age. Because this study includes the largest cohort of childhood cancer survivors with prospective medical/clinical evaluation of health outcomes, it is extremely hard to find another cohort that has similarly ascertained health phenotypes 10 . In such situations, it is imperative that an innovative and robust internal validation approach is undertaken to validate the top SNPs identified through GWAS 10,11 .…”
Section: Introductionmentioning
confidence: 99%